PENYULUHAN DAN PEMASANGAN SISTEM PEMANENAN AIR HUJAN (PAH) DI DESA SUKALUYU - KARAWANG - Wijayanti, Asih; Iswanto, Bambang; Wartaman, Anita Sitawati; Marendra, Sheilla Megagupita Putri (JUARA: Jurnal Wahana Abdimas Sejahtera, 2023)
The source of clean water for the people of Sukaluyu Village, Telukjambe Timur District, Karawang Regency comes from surface water, namely from the Drinking Water Company (PAM), and some comes from ground water. Excessive groundwater withdrawal will cause the volume of groundwater to shrink. On the other hand, during the rainy season, due to excess water discharge, the problem that often arises is flooding. These floods can occur in areas close to rivers. One alternative to fulfilling the need for clean water in Sukaluyu Village is by making Rainwater Harvesting with appropriate technology. Rainwater Harvesting is a way to collect and store rainwater from rooftops when it rains. The method used is socialization of PAH installation online. The purpose of this Community Service activity is to invite the people of Sukaluyu Village to actively participate in creating alternative appropriate technologies. The method of carrying out this activity is to conduct counseling and training on installing the PAH tool system online. The results of the implementation of this PKM activity can be concluded that this PKM activity can add insight to KSM Friends of the Environment members and the community in Sukaluyu Village, Teluk Jambe Timur District, Karawang Regency regarding the benefits of rainwater and the installation of rainwater harvesting system tools which can be used as an alternative source of clean water